Pre- and Post-diagnosis Diabetes as a Risk Factor for All-Cause and Cancer-Specific Mortality in Breast, Prostate, and Colorectal Cancer Survivors: a Prospective Cohort Study - Tao, Huan; O'Neil, Adrienne; Choi, Yunseon; Wang, Wei; Wang, Junfeng; Wang, Yafeng; Jia, Yongqian; Chen, Xiong (Frontiers in Endocrinology, 2020)
Objective The relationship between diabetes and all- and cause-specific mortality in individuals with common cancers (breast, colorectal and prostate) remains both under-researched and poorly understood. Methods Cancer survivors (N=37,993) from the National Health Interview Survey with linked data retrieved from the National Death Index served as our study participants. Cox proportional-hazards models were used to assess associations between pre- and post-diabetes and all-cause and cause-specific mortality. Results Over a median follow-up period of 13 years, 2,350 all-cause, 698 cancer and 506 CVD deaths occurred. Among all cancer survivors, patients with diabetes had greater risk of: all-cause mortality (hazard ratio (HR) 1.35, 95% CI=1.27-1.43), cancer-specific mortality (HR: 1.14 , 95% CI=1.03-1.27), CVD mortality (HR: 1.36, 95% CI=1.18-1.55), diabetes related mortality (HR: 17.18, 95% CI=11.51-25.64), and kidney disease mortality (HR: 2.51, 95% CI=1.65-3.82), compared with individuals without diabetes. The risk of all-cause mortality was also higher amongst those with diabetes and specific types of cancer: breast cancer (HR: 1.28, 95% CI=1.12-1.48), prostate cancer (HR: 1.20, 95% CI=1.03-1.39) and colorectal cancer (HR: 1.29, 95% CI=1.10-1.50). Diabetes increased the risk of cancer-specific mortality among colorectal cancer survivors (HR: 1.36, 95% CI=1.04-1.78) compared to those without diabetes. Diabetes was associated with higher risk of diabetes-related mortality when compared to non-diabetic breast (HR: 9.20, 95% CI=3.60-23.53), prostate (HR: 18.36, 95% CI=6.01-56.11) and colorectal cancer survivors (HR: 12.18, 95% CI=4.17-35.58). Both pre- and post-diagnosis diabetes increased the risk of all-cause mortality among all cancer survivors. Cancer survivors with diabetes had similar risk of all-cause and CVD mortality during the second 5 years of diabetes and above 10 years of diabetes as compared to non-diabetic patients. Conclusions Diabetes increased the risk of all-cause mortality among breast, prostate, and colorectal cancer survivors, not for pre- or post-diagnosis diabetes. Greater attention on diabetes management is warranted in cancer survivors with diabetes.